Photoelastic Analysis of Stress Distribution With Different Implant Systems - Pellizzer, Eduardo Piza [UNESP]; Carli, Rafael Imai [UNESP]; Falcon-Antenucci, Rosse Mary [UNESP]; Verri, Fellippo Ramos [UNESP]; Goiato, Marcelo Coelho [UNESP]; Villa, Luiz Marcelo Ribeiro [UNESP] (Allen Press Inc, 2014)
The aim of this study was to evaluate stress distribution with different implant systems through photoelasticity. Five models were fabricated with photoelastic resin PL-2. Each model was composed of a block of photoelastic resin (10 x 40 x 45 mm) with an implant and a healing abutment: model 1, internal hexagon implant (4.0 X 10 mm; Conect AR, Conexao, Sao Paulo, Brazil); model 2, Morse taper/internal octagon implant (4.1 x 10 mm; Standard, Straumann ITI, Andover, Mass); model 3, Morse taper implant (4.0 x 10 mm; AR Morse, Conexao); model 4, locking taper implant (4.0 x 11 mm; Bicon, Boston, Mass); model 5, external hexagon implant (4.0 x 10 mm; Master Screw, Conexao). Axial and oblique load (45) of 150 N were applied by a universal testing machine (EMIC-DL 3000), and a circular polariscope was used to visualize the stress. The results were photographed and analyzed qualitatively using Adobe Photoshop software. For the axial load, the greatest stress concentration was exhibited in the cervical and apical thirds. However, the highest number of isochromatic fringes was observed in the implant apex and in the cervical adjacent to the load direction in all models for the oblique load. Model 2 (Morse taper, internal octagon, Straumann ITI) presented the lowest stress concentration, while model 5 (external hexagon, Master Screw, Conexao) exhibited the greatest stress. It was concluded that Morse taper implants presented a more favorable stress distribution among the test groups. The external hexagon implant showed the highest stress concentration. Oblique load generated the highest stress in all models analyzed.
Keywords: dental implant; implant systems; biomechanics; photoelasticity